Prosedur Pengelolaan Arsip Elektronik Melalui Website SIPANDU di Bakorwil III Malang - Yuniarta Dwi Nurhakiki; Erlangga Andi Sukma (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of information technology has encouraged government institutions to adopt electronic records management to improve administrative effectiveness. However, archival information systems require not only technological support but also clear procedures to ensure that records management processes are carried out consistently and systematically. This study aims to describe the procedures for electronic records management through the Sistem Pengelolaan Arsip Terpadu (SIPANDU) website at Bakorwil III Malang. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation studies. The results show that electronic records management at Bakorwil III Malang requires procedural standardization, particularly in records registration, records filing, and records reporting. The analysis indicates that the registration and filing procedures support the document input process, although both have different functions: registration focuses on recording basic archival metadata, while filing focuses on completing file contents and organizing records. Meanwhile, the reporting procedure supports records retrieval through data searching and report downloading. These procedures contribute to a more systematic, consistent, and integrated electronic records management process through the SIPANDU website.